Capital Accumulation, the frame behind the Boyacá west conflict - García-Norato, José Florentino; García-Norato, Myriam Emilce (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The purpose of this paper is to establish the influence of the mining development in the conflict on the western area of Boyacá, Colombia. The research is framed under the qualitative paradigm, defining as main indicators the accumulation of large capitals and social control exercised by business conglomerates, from the period between 2010 and 2017. The results indicate that the configuration of the conflict on the west of Boyacá responds to the interest of the accumulation of large capitals by the companies that traditionally operate in the area. In addition, the absence of the State is evident, reflected in the lack of control of the companies that have the exploitation of the mines, as well as in the constant violation of the human rights of the citizens of the region. Finally, the intervention of the multinationals appears as an emerging phenomenon that will need constant control by the State.